Pengaruh Metode Demonstrasi Berbantuan Video Screencast Terhadap Hasil Belajar Siswa Kelas VIII pada Mata Pelajaran Informatika di SMPN 3 Kedungwaru - Dianawati, Wahyu; Panggayuh, Vertika; Indrakusuma, H. Abdul Haris (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of the Screencast video-assisted demonstration method on the Informatics learning outcomes of eighth-grade students of SMPN 3 Kedungwaru. The study used a quantitative approach with a quasi-experimental design and a Nonequivalent Control Group Design. The study population was 179 eighth-grade students, with a sample of 58 students consisting of class VIII D as the experimental class and VIII E as the control class. The sample was selected using a purposive sampling technique. Data were collected through a learning outcome test in the form of 26 multiple-choice questions that have been declared valid and reliable with a Cronbach's Alpha value of 0.936. Data analysis included normality, homogeneity, and hypothesis testing using the Mann-Whitney U Test with the help of IBM SPSS Statistics 25. The results showed that the average posttest of the experimental class was 83.95, higher than the control class of 57.03. The results of the hypothesis test showed an Asymp. Sig. (2-tailed) value of 0.000 <0.05, so there was a significant difference in learning outcomes between the two groups. Thus, the Screencast video-assisted demonstration method effectively improves the Informatics learning outcomes of class VIII students.